“ETIKA PENGELOLAAN BIG DATA DI DUNIA USAHA: PERSPEKTIF LITERATUR TERHADAP PRIVASI DAN TANGGUNG JAWAB SOSIAL” - Fitri Handayani Harahap; Muhammad Irwan Padli Nasution (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2025)
The advancement of digital technology has brought significant changes to the business world, particularly in the collection, analysis, and utilization of customer big data. Amid efforts to maximize the strategic value of big data, major ethical challenges have emerged, especially concerning privacy and corporate social responsibility. This article is a literature study that aims to examine how ethics are integrated into the management of customer big data in the business sector. Using a qualitative approach based on a literature review of various journals and scientific publications from the past ten years, the study finds that ethical integration in big data management remains a developing and complex issue. Most companies still lack strong ethical guidelines in handling consumer data, which poses risks to individual privacy and potential social harm. This article suggests that businesses should establish data governance rooted in ethical principles, including transparency, accountability, and the protection of customers’ digital rights.